Strategic Leadership of School Principals in Improving Teacher Work Culture in Islamic Secondary Schools - Huda, Nurul; Subandi, Subandi; Amirudin, Amirudin (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2025)
The principal holds a strategic role in shaping teacher work culture to enhance the quality of education in Islamic schools. This research aims to describe the leadership strategies employed by the principal of MTs Muhammadiyah Bandar Lampung in strengthening teachers’ work culture. Using a descriptive qualitative approach, data were collected through interviews, observations, and document analysis, and analyzed using the Miles and Huberman model. The results show that the principal implements a participatory and religious leadership model by integrating Muhammadiyah values into daily practices, such as congregational prayers, religious mentoring, and character development. The CECC strategy (Check, Evaluate, Consult, Control) is applied systematically to improve teacher discipline, professionalism, and responsibility. Moreover, teachers are involved in decision-making and receive welfare support through fair task distribution, incentives, and social protection. These efforts have successfully built a disciplined, collaborative, and spiritually grounded teacher work culture, contributing significantly to the improvement of educational quality at the school.